Adenosine Deaminase activity in Plasma of Children with Acute Lymphoblastic Leukemia - Mishra, SK; Sah, JP; Awasthi, G; Sharma, R (Journal of Nepal Health Research Council, 2010)
Background: Acute Lymphoblastic Leukemia is stem cell malignant disorder characterized by overproduction of Lymphoblast in Bone marrow that eventually spill into circulation. Adenosine Deaminase activity has been shown to increase in most chronic conditions especially lymphocytic proliferation and other malignancies. The objective of the study was to determine the concentration of plasma Adenosine Deaminase in children suffering from Acute Lymphoblastic Leukemia. Methods: Adenosine Deaminase activity in plasma of ALL and normal children under 14 years of age visiting was measured. Total Leukocyte count and absolute lymphocyte count were performed in hematology laboratory of Kanti Children's Hospital. Results: Adenosine Deaminase activity in plasma of children suffering from Acute Lymphoblastic Leukemia was higher than non- ALL children with leukocytosis and lymphocytosis and healthy Control groups without leukocytosis. The plasma ADA level was 48.85 ±2.42 IU/L in ALL patients, which was significantly higher by student's two-tailed t-test (P=0.002) than plasma ADA level in control subject (mean ADA=39.72 IU/L Std. error mean =1.27 IU/L). Increased plasma ADA level was found in non-ALL with leukocytosis and lymphocytosis and ALL patients. Conclusions: Adenosine Deaminase activity in plasma of children suffering from Acute Lymphoblastic Leukemia was increased. Hence plasma ADA can serve as another serum biomarker in addition to other haematological markers and clinical characteristics of acute lymphoblastic leukemia (ALL). It is easy to perform in small laboratories and will be beneficial as a non interventional prognostic marker. Key words: acute lymphoblastic leukemia; absolute lymphocyte count; adenosine deaminase. DOI: 10.3126/jnhrc.v7i2.3014 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 93-97